The Changing East Asian Security Landscape Challenges, Actors and Governance (Edition ZfAS, 2018)
This book examines a highly relevant empirical issue in International Rela- tions. A group of renowned scholars analyzes the new dynamics of East Asian Security and its respective governance structure challenging the conventional wisdom that the US as the traditional offshore balancer in the region is still the most definitive element in determining the outcomes in the region. Since the US pivot and other actors' responses to it the security landscape has changed in form, size and function. In order to analyze and explain these changes, the authors apply hypotheses derived from Inter- national Relations middle range theories (i.e. soft and hard balancing) to cases of bilateral and multilateral security governance in East Asia. Contents •The US pivot and its implications for the current East Asian Security Architecture •Intra-Asian Defense Cooperation and the Emergence of a 2nd Order Security Architecture in the Asia-Pacific •Sino-American Competition as Security Suppliers in the Asia-Pacific •Paul Kennedy's Conception of Great Power Rivalry and US-China Relations in the Obama Era etc. Target Groups Lecturers and students of international politics The Editors Dr. Stefan Fröhlich is Professor for International Politics at Friedrich-Alexan-der University Erlangen-Nürnberg, Germany. Dr. Howard Loewen is Visiting Professor of Political Science at Friedrich-Alexander University Erlangen-Nürnberg, Germany.